2019
DOI: 10.3390/molecules24203728
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Indole-Based Chalcones: A Structural and Theoretical Analysis

Abstract: The crystal structures of five new chalcones derived from N-ethyl-3-acetylindole with different substituents were investigated: (E)-3-(4-bromophenyl)-1-(1-ethyl-1H-indol-3-yl)prop-2-en-1-one (3a); (E)-3-(3-bromophenyl)-1-(1-ethyl-1H-indol-3-yl)prop-2-en-1-one (3b); (E)-1-(1-ethyl-1H-indol-3-yl)-3-(4-methoxyphenyl)prop-2-en-1-one (3c); (E)-1-(1-ethyl-1H-indol-3-yl)-3-mesitylprop-2-en-1-one (3d); and (E)-1-(1-ethyl-1H-indol-3-yl)-3-(furan-2-yl)prop-2-en-1-one (3e). The molecular packing of the studied compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Michaël-type Friedel–Crafts addition of nucleophiles (especially indoles) with electron-deficient alkenes are fundamentally important chemical transformations [ 20 , 21 , 22 , 23 , 24 ]. These methods have extensive uses in the scientific work on a number of potential nucleophilic species.…”
Section: Resultsmentioning
confidence: 99%
“…Michaël-type Friedel–Crafts addition of nucleophiles (especially indoles) with electron-deficient alkenes are fundamentally important chemical transformations [ 20 , 21 , 22 , 23 , 24 ]. These methods have extensive uses in the scientific work on a number of potential nucleophilic species.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the inhibition of auto agy-flux by chloroquine-sensitized cells to death upon MIPP and MOMIPP treatment visible in the decreased metabolic activity of the cells and the increased apoptosis le These are the first studies of this type to show the antitumour effects of indole-based c cones on fibrosarcoma cells. Previous research reported that specific indole-based c cones can cause cell death in glioblastoma, gastric carcinoma cells, and triple-nega breast cancer cells MDA-MB-231 [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Pyrimidine-indole derivatives have been reported to inhibit α-glucosidase and α-amylase ( 23 ). Among the nitrogen-containing heterocycles, indole derivative compounds have been reported to have a wide range of biological activities, including antibacterial, antifungal, anticancer, and anti-HIV properties ( 24 27 ). However, to our knowledge, there are no inhibitors with chemical structures similar to that of hit B and its derivatives that target other β-glucosidases.…”
Section: Discussionmentioning
confidence: 99%